Radioatividade natural em solos canavieiros do estado de São Paulo - Fernandes, Elisabete A. de Nadal; Ferraz, Epaminondas S. B.; Oliveira, Helder de (Sociedade & Natureza, 2021)
Radioatividade natural em solos canavieiros do estado de São Paulo